Relationship between optimism, emotional intelligence, and academic resilience of nursing students: the mediating effect of self-directed learning competency - Hwang, Eun Hee; Kim, Kon Hee (Frontiers in Public Health, 2023)
Background: The evolution toward future education following the 4th industrial revolution and the coronavirus disease 2019 (COVID-19) pandemic have changed nursing education dramatically. Online classes have become a new paradigm of education, and are expected to develop and be maintained in various forms even after the end of COVID-19. Therefore, attention is focused on finding ways to improve learners' achievements in a distance learning environment. This study aimed to examine the mediating effects of self-directed learning competency on the relationships between optimism, emotional intelligence and academic resilience among nursing students. Methods: A cross-sectional descriptive design was conducted using convenience sampling of 195 nursing students in South Korea. Data were analyzed with descriptive statistics, Pearson’s correlation coefficients, multiple regression, and mediation analysis using SPSS/WIN 26.0 program. Results: There were significant positive correlations among self-directed learning competency, optimism, emotional intelligence and academic resilience. The self-directed learning competency acts as a mediator in explaining relationship between optimism, emotional intelligence and academic resilience respectively. Conclusion: This study provides the evidence for the role of self-directed learning competency in the relationship between optimism, emotional intelligence and academic resilience in nursing students. Rapid changes in education are inevitable due to changes in clinical settings and the impact of repeated infectious disease outbreaks including the COVID-19 pandemic. This study suggests strengthening positive psychology and self-directed learning capability of nursing students as a strategy to prepare for changes in education and clinical areas.